2016
DOI: 10.4317/medoral.20938
|View full text |Cite
|
Sign up to set email alerts
|

Complications in the use of the mandibular body, ramus and symphysis as donor sites in bone graft surgery. A systematic review

Abstract: BackgroundTo develop a systematic review by assessing and comparing the different complications that occurs in bone graft surgery using the mandibular body, ramus and symphysis as donor sites.Material and MethodsIn order to respond to the following question, a systematic review was developed: does the use of intraoral mandibular body and ramus as donor sites in bone graft surgery, produce fewer and less severe complications in comparison to the use of the mandibular symphysis in patients that present bone reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 24 publications
0
35
0
Order By: Relevance
“…A few cases have reported severe complications and even life‐threatening. A systematic review reported the most common complications were temporary sensory alterations in the anterior teeth (33.87%), followed by sensory alterations of the skin and mucosa (18.57%) . A prospective clinical study reported neurosensory disturbances following bone harvesting were found in 43.3% of the patients .…”
Section: Discussionmentioning
confidence: 99%
“…A few cases have reported severe complications and even life‐threatening. A systematic review reported the most common complications were temporary sensory alterations in the anterior teeth (33.87%), followed by sensory alterations of the skin and mucosa (18.57%) . A prospective clinical study reported neurosensory disturbances following bone harvesting were found in 43.3% of the patients .…”
Section: Discussionmentioning
confidence: 99%
“…28 However, especially in the presence of mandibular anterior teeth, dental necrosis in the region and the risk of numbness are among the disadvantages of this practice. 29 In our case, the mandibular anterior region was chosen since the region is completely edentulous, CBCT examinations show that the area is not only sufficient as donor site but also implant placement in the later stage, and besides bilateral access will be required for the other alternative donor site, the ramus region which was already thin for the patient. Despite the proven success of implants placed in grafted areas, the number of case reports or studies carried out in the long-term follow-up of All-on-4 concept in the grafted regions in the literature is very small.…”
Section: Prosthetic Phasementioning
confidence: 99%
“…3 Within the mouth, the mandible tends to present more sources than the maxilla, and the anterior border of the ramus, the mandibular body, or the symphysis are almost always preferred as donor sites. 8 Mandibular bone grafts result in better-quality bone and a shorter healing period than other methods of bone repair. 4 Other advantages include minimal resorption (5%-28%), 9,10 no need for hospitalization (and thus lower cost), 6 minimal discomfort, 11 no alteration in ambulation, and the absence of cutaneous scars.…”
Section: Introductionmentioning
confidence: 99%